2018
DOI: 10.1016/j.neulet.2018.04.046
|View full text |Cite
|
Sign up to set email alerts
|

Influence of foot position and vision on dynamic postural strategies during the “grand plié” ballet movement (squatting) in young and adult ballet dancers

Abstract: The effect of foot position was greatest with EO. The parallel position was less stable. The YD were more unstable in the parallel position, particularly with EC. For both groups, the lack of vision increased instability. These results show the importance of integrating balance training in a variety of foot positions and visual conditions, particularly during the initial stages of training to prevent injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
(78 reference statements)
0
8
0
Order By: Relevance
“…There is a general consensus in the literature that dancers use proprioceptive and visual stimuli as their fundamental sensory inputs 2 . Their balancing abilities are superior to those of non-dancers when their eyes are open, but not with eyes closed, suggesting that the ability to change acutely from one balancing mechanism to another is not sophisticated 2,5,8,9,28 . This fact may explain the greater changes observed in the stabilometry of the dancers group when compared to the open and closed eyes conditions.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…There is a general consensus in the literature that dancers use proprioceptive and visual stimuli as their fundamental sensory inputs 2 . Their balancing abilities are superior to those of non-dancers when their eyes are open, but not with eyes closed, suggesting that the ability to change acutely from one balancing mechanism to another is not sophisticated 2,5,8,9,28 . This fact may explain the greater changes observed in the stabilometry of the dancers group when compared to the open and closed eyes conditions.…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, dynamic balance strategies seem to be influenced by growth accelerations, which can distort proprioceptive references and representations of the body. In static balance, young dancers' postural control is less efficient than that of adults, and they are more dependent on vision 8 . Classical ballet dancers must have sophisticated balance mechanisms to effectively position themselves during the complex choreographic sequences of their performances, with multidirectional activities at different amplitudes and angles of rotation 9 .…”
mentioning
confidence: 99%
“…Studies on ankle kinematics [ 20 ] observed that a significant decrease in the height of the medial longitudinal arch can induces decreases in the body stability during landing in jumping movements [ 46 ]. Thus, the foot support base is a main key point for integrating greater body stability and balance for dancers [ 7 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…This scientific evidence reveals that the initial understanding of the foot support base comes from the characteristic of the foot posture, which most studies identify as a pronation foot posture [ 7 , 18 , 21 ]. However, no scientific studies have examined this issue with regard to dancers with symptoms of low back pain, which makes it difficult to discuss the present findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation